A method for sensitive staining of DNA in polyacrylamide gels using basic fuchsin. (June 2013) - Chen, Mao; Cong, Wei-Tao; Zhou, Xuan; Zhu, Zhong-Xin; Ye, Wei-Jian; Ling, Jin; Ni, Mao-Wei; Jin, Li-Tai
Background : PAGE is a widely used analytical method to resolve components of a DNA mixture based on their size. Various DNA visualization methods including fluorescence, visible dye and silver have been used for the detection of gel-separated DNA, with each having different advantages and disadvantages in terms of sensitivity, safety and simplicity.Results : A fast and sensitive visible dye-based staining method for DNA in polyacrylamide gels using basic fuchsin (BF) is described. As low as 10–20 pg of DNA can be visualized within 10 min; the sensitivity is fourfold more sensitive than that of SYBR ® Gold stain, the most sensitive commercial fluorescent probe, but similar to silver staining kit from GE Healthcare. In addition, the mechanism studies suggest that the interaction of BF with DNA is mainly contributed by non-intercalative binding mode.Conclusion : By comprehensive studies of this visible dye-based protocol, we concluded that BF stain is a fast and sensitive method currently available for detecting DNA in polyacrylamide gels.